Developmental roles of the Mi-2/NURD-associated protein p66 in Drosophila. - Kon, C.; Cadigan, K.M.; da Silva, S.L.; Nusse, R. (Genetics, 2005)
The NURD and Sin3 histone deacetylase complexes are involved in transcriptional repression through global deacetylation of chromatin. Both complexes contain many different components that may control how histone deacetylase complexes are regulated and interact with other transcription factors. In a genetic screen for modifiers of wingless signaling in the Drosophila eye, we isolated mutations in the Drosophila homolog of p66, a protein previously purified as part of the Xenopus NURD/Mi-2 complex. p66 encodes a highly conserved nuclear zinc-finger protein that is required for development and we propose that the p66 protein acts as a regulatory component of the NURD complex. Animals homozygous mutant for p66 display defects during metamorphosis possibly caused by misregulation of ecdysone-regulated expression. Although heterozygosity for p66 enhances a wingless phenotype in the eye, loss-of-function clones in the wing and the eye discs do not have any detectable phenotype, possibly due to redundancy with the Sin3 complex. Overexpression of p66, on the other hand, can repress wingless-dependent phenotypes. Furthermore, p66 expression can repress multiple reporters in a cell culture assay, including a Wnt-responsive TCF reporter construct, implicating the NURD complex in repression of Wnt target genes. By co-immunoprecipitation, p66 associates with dMi-2, a known NURD complex member.